Verbal connectives and their argumentative impact in the sayings of Ahl al-Bayt (Peace be upon them) in the Book Mizan al-Hikmah by Muhammad al-Ray Shahri - Al-Hamdani, Raba’a Hussein Mahdi; Harith, Mohammed Saleh Yaseen (Edelweiss Applied Science and Technology, 2024)
In order for arguments to be effective and influential within the rhetorical text, and to achieve the desired result, they need verbal links that connect the arguments to each other, and through which the meaning and form are coherent, leading to the overall coherence and cohesion of the text. Argumentative links coordinate the text and link arguments to conclusions, which results in convincing the recipient, who is the goal of the argumentative process. The letter (Fa) performs an argumentative function by linking the argument to the conclusion. It indicates reasoning and inference, in addition to arranging the arguments. It is also one of the links that the speaker employs in his speech to link between successive events, or between two issues that are close in meaning to the events. The tool (but) is one of the argumentative links that indicates a correction, so it works to negate a statement and prove something else, and it is brought to remove what the recipient imagines or what comes to his mind of the illusions accompanying the first argument, which is the weaker argument than the argument that comes after the link (but). That The link (rather) is one of the links that the speaker uses to move from one argument to another stronger argument, without invalidating what came before. The various argumentative links deepened and multiplied the meaning, and transformed the argumentative discourse into a rich semantic focus, which contributed to making the argumentation achieve its persuasive goal, through optimal investment and skillful selection of the argumentative link that is consistent with the context of the speech.